Taman Edukasi Herbal Objek Wisata Sendang Seloaji Randualas, Kare Sebagai Upaya Edukasi Masyarakat dan Daya Tarik Wisatawan - Rizki Amalia; Naila Oktavia Nisa; Lutfi Nurhidayah; Muslimah Mubarokah; Firnanda Rayhan Syah Falaini; Arum Suproborini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Sendang Seloaji Tourist Attraction Herbal Education Park which is located in Slaji Hamlet, Randualas Village, Kare District, Madiun Regency, the herbal education park in the Sendang area has various types of herbal plants such as Mint (Mentha piperita), Stevia (Stevia rebaudiana), Cat's Whiskers (Orthosiphon aristatus), Lavender (Lavandula officinalis), Telang (Clitoria ternatea), Ginger (Zingiber officinale), Nerve leaves (Hemigraphis alternate), Seven Blade Needles (Pereskia bleo (Kunth) D.C.), Red Betel (Piper ornatum), green betel (Piper betle L.), Turmeric (Curcuma Longa), and lemongrass (Cymbopogon citratus). The aim of this community service is to increase public knowledge about the benefits of medicinal plants and increase the attraction of tourists to visit the Sendang Seloaji tourist attraction. The methods used in this community service are socialization/counseling on toga plants and the practice of creating a herbal educational garden. As a result of this service, people are starting to understand the various types of herbal plants that can be used as medicine. They now better understand the importance of healthy living and understand natural treatment alternatives that are more affordable and have minimal side effects, have higher motivation to learn, and are more enthusiastic about planting herbal plants. This program proves that a learning approach that directly involves the community can build unity among each other and increasing the number of tourists at the Sendang Seloaji tourist attraction is expected to improve the economy of the Randualas community.